2021
DOI: 10.3390/ijerph18168817
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life in Patients with Health Conditions in Lebanese Community Setting

Abstract: Background: The measurement of health-related quality of life (HRQoL) provides utility scores that could be used for health economics assessment. The aim of this study was to measure HRQoL in Lebanese patients with certain medical conditions, and to determine demographic and medical factors affecting such health utility scores. Method: This was a prospective cross-sectional pilot study conducted to gather information on the socioeconomic status, health condition and quality of life of participants with common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
2
2
0
Order By: Relevance
“…This could however be explained by the inclusion of a higher percentage of patients with severe MS − 28.3% for the Netherlands and 30% for the UK, compared with 13% in our study. The mean utility for the EQ-5D-5L in a recent study using the UK value set on Lebanese patients with diabetes and cardiovascular diseases was 0.76, similar to our result [31].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This could however be explained by the inclusion of a higher percentage of patients with severe MS − 28.3% for the Netherlands and 30% for the UK, compared with 13% in our study. The mean utility for the EQ-5D-5L in a recent study using the UK value set on Lebanese patients with diabetes and cardiovascular diseases was 0.76, similar to our result [31].…”
Section: Discussionsupporting
confidence: 90%
“…Utility scores in our study, derived from the EQ-5D-5L and MusiQoL, were similar to existing QoL studies in Lebanon [19,20,31].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Results from the study indicated that the high-income group have higher life satisfaction than the middle-income group, and the middle-income group has higher life satisfaction than the low-income group. Likewise, Dimassi et al (2021) showed that Lebanese adults with higher socioeconomic classes had a considerably better QoL than those of lower socioeconomic classes.…”
Section: Qol and Incomementioning
confidence: 99%